Overburden stress evolution characteristics and prediction of disasters with across-gully mining - Wang, Hongwei; Jiang, Baolin; Jiao, Jianqiang; Li, Yanjun (Frontiers in Earth Science, 2023)
The coal water co-mining of shallow coal seams in loess gully area of northern Shaanxi is affected by coupling effect of overburden structure and topography. The development characteristics of mining fracture are complex and can induce mining and environmental disasters. To predict disasters formation, taking the 113101 working face of Kunyuan coal mine as background, numerical simulation, physical similarity simulation experiment, and theoretical analysis methods were used to analyze the mining gully of a shallow coal seam in loess gully areas. Based on the dynamic evolution characteristics of stress at different locations,the formation positions and dynamic development and evolution processes of various fractures were studied, disaster-causing mechanism and interactions of disasters were revealed, and comprehensive methods were proposed.The results showed that in the across-gully mining, the maximum horizontal compressive stress at the bottom of Gully No.2 was approximately 20.00 MPa, the maximum horizontal tensile stress of the reverse slope section was approximately 1.50 MPa, the width of the F5 fracture of Gully No.2 was 46.00 cm, and the elevation difference was up to 52.00 cm. Working face across-gully mining formed tensile fractures in most areas, collapsed fractures at the gully bottom, and extruded fractures in the reverse slope section. The fracture at the gully bottom could easily induce water-sand inrush and roof cutting pressure and the slope fracture could induce gully-induced landslide. According to the mechanisms and distribution areas of fracture disasters, the disaster areas were divided into the water-sand inrush area at the gully bottom, roof caving and supports crushing area at the gully bottom and at base of the slope section, and landslide area at the upper part of the slope section and reverse slope section. Appropriate prevention and control measures were proposed, such as interception of surface water in the upstream, slope reinforcement in the middle and upper part of the downhill section, artificial roof cracking in the middle and upper part of the downhill section, and grouting reinforcement at the gully bottom and slope toe of the downhill section. These measures were proven to effectively guarantee the safe and efficient mining efficiency of the working face.